Gender Role Reversals in Marginal Space: Uncovering Female Breadwinners in Semi-Arid Rural Indonesia Through a Socio-Geographic Lens - Chalia Chistella; Selamat Riadi; Kurnia Maulidi Noviantoro; M Rizqon Al Musafiri; Bejo Apriyanto; Inaz Khusnul Khotimah (Universitas Negeri Gorontalo, 2025)
This research explores the gender shifts occurring in Oeseli, a remote village in East Nusa Tenggara, Indonesia. In this village, women are the primary breadwinners due to socio-geographical conditions. Through a socio-geographic lens, this research explores how semi-arid climate and geographical boundaries of Sawu Sea affects an economy and leads to shifting gender roles. Through in-depth interviews and observations, the research highlights women's dual role as caregivers and breadwinners, which is exacerbated by men's migration in seeking greater economic opportunities outside the village. Despite their significant contributions to the agriculture, livestock, and fisheries sectors, women in Oeseli face various constraints, including local resource, skill, and infrastructure limitations that hinder their full economic potential. Conceptually, this research reveals how semi-arid environmental pressures drive male labor migration and reconstruct gender roles, particularly for rural areas with limited natural resources such as Oeseli. It provides a new socio-geographical explanation of how ecological constraints lead to gender shifts. This qualitative case study research emphasizes an imperative for interventions that empower women, address gender inequalities, and foster sustainable development. By bridging the traditional cultural practices with the evolving socio-economic realities, this research advocates for a more equitable distribution of labor and resources. In the end, the research aims to increase community resilience and achieve gender equality in Oeseli and similar contexts.